Distribution of 137Cs Radionuclide in Industrial Wastes Effluents of Gresik, East Java, Indonesia - Muslim Muslim; H. Suseno; F. Rafsani (Atom Indonesia, 2015)
The distribution of anthropogenic radionuclides 137Cs was measured from industrial waste effluent of Gresik to Gresik Sea in east Java, Indonesia. The activity of 37Cs detected at all stations was much lower than in northeast Japan both before and after NPP Fukushima accident. This indicated that in Gresik industrials waste did not consist of 137Cs. The lowest activity 137Cs occurred at the station nearest to the industrial waste effluent that contained some particle ions that were able to scavenge 137Cs and then precipate this radionuclide. Furthermore, the greatest 137Cs occured at the station that has high current speeds that stirred up sediment to release 137Cs in seawater as a secondary source. The lowest salinity did not effect on the activity of 137Cs even though the lowest salinity and activity 137Cs occured at the same station.Received: 04 October 2014; Revised: 09 March 2015; Accepted 23 March 2015